Voluntary agreements for the achievement of sustainable development goals : Dutch Green Deals and WRAP agreements - Salo, Eftimiya (2016)
Voluntary environmental agreements (VEAs) are attracting considerable attention due to the complexity of the current environmental issues. Fostering collaboration between public and private parties is considered an effective means for achieving sustainable development goals. Even though VEAs have been studied in the past, little research has focused on the novel and successful agreements from the Netherlands (Green Deals) and the UK (WRAP agreements). Thus, this study aims at filling this gap of knowledge by exploring the way the Dutch Green Deals and WRAP agreements work and how their efficiency is measured.